2018
DOI: 10.3748/wjg.v24.i46.5189
|View full text |Cite
|
Sign up to set email alerts
|

Chinese consensus on management of tyrosine kinase inhibitor-associated side effects in gastrointestinal stromal tumors

Abstract: Tyrosine kinase inhibitors (TKIs) have improved the overall survival of patients with gastrointestinal stromal tumors (GISTs), but their side effects can impact dose intensity and, consequently, the clinical benefit. To date, no guideline or consensus has been published on the TKI-associated adverse reactions. Therefore, the Chinese Society of Surgeons for Gastrointestinal Stromal Tumor of the Chinese Medical Doctor Association organized an expert panel discussion involving representatives from gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…Besides, elimination of resistant lesion is believed in favor of reintroduction of IM management in the context that second-line therapies are frequently not as well-tolerated as that of IM. [ 24 26 ] Concerning synchronous/metachronous liver metastases, Y-Jiang Ye and colleagues found that combination of surgery with TKI treatment may be the most effective strategy for GIST patients with liver metastases. [ 27 ] It has been reported in a retrospective study shown that surgical resection of liver metastases and primary lesion in GIST patients combined with IM may be associated with prolonged OS.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, elimination of resistant lesion is believed in favor of reintroduction of IM management in the context that second-line therapies are frequently not as well-tolerated as that of IM. [ 24 26 ] Concerning synchronous/metachronous liver metastases, Y-Jiang Ye and colleagues found that combination of surgery with TKI treatment may be the most effective strategy for GIST patients with liver metastases. [ 27 ] It has been reported in a retrospective study shown that surgical resection of liver metastases and primary lesion in GIST patients combined with IM may be associated with prolonged OS.…”
Section: Discussionmentioning
confidence: 99%
“…56 The consensus in China suggests that reducing the dose of SU from 50 mg/d to 37.5 mg/d, can reduce the degree of neutropenia or thrombocytopenia. 57 In many solid tumors, increasing the dose will get better RFS and OS. A study in patients with mRCC or GIST confirmed that increasing the dose of SU can improve RFS, OS, and have a higher chance of antitumor response, but at the same time, it also increases the risk of adverse effects.…”
Section: Dovepressmentioning
confidence: 99%
“…Imatinib is generally well tolerated in GIST patients, and most adverse effects do not need imatinib dose reduction or interruption (24,25). However, dose reduction is required by 40% of GIST patients, and the discontinuation rate of imatinib is as high as 49% in these patients (14,(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining a continuous and sufficient imatinib dose is important to achieve optimal clinical outcomes; therefore, adequate management of imatinib-associated adverse events is crucial (25,28). Skin rash commonly presenting as erythematous and maculopapular lesions occurs in up to 35% of GIST patients treated with imatinib, and approximately 10% of patients experience grades 3-4 skin rash (9,10,24). The underlying mechanism of imatinibrelated skin rash is still unclear, but based on the high frequency, it is believed to be due to the blockade of the c-kit protein, which is normally present in the skin, rather than hypersensitivity (28).…”
Section: Introductionmentioning
confidence: 99%